Artificial Intelligence Sebagai Efisiensi Proses Kreatif Desainer DKV (Studi Kasus: Ilustrasi Maskot dan Skrip Video Profil Desa Wisata Mertelu) - Farizul Haq; Raden Hadapiningrani Kusumohendrarto (MDP Student Conference, 2026)
This study examines the role of Artificial Intelligence (AI) in improving the efficiency of creative workflows in Visual Communication Design (VCD) through a case study on mascot illustration design and promotional video script development for Mertelu Tourism Village, Gunungkidul. A qualitative approach with the design thinking method was employed, consisting of the empathize, define, ideate, prototype, and test stages. AI tools were utilized for brainstorming, data processing, scriptwriting, shot angle planning, and mascot pose exploration. The findings indicate that AI significantly reduces production time, optimizes creative workflows, and enhances idea exploration while maintaining the designer’s role as the primary creative decision-maker. This research highlights AI as a strategic creative assistant that supports efficiency and productivity in sustainable digital design practices.